First record of Dorcadion (Pedestrodorcadion) kaimakcalanum (Jureček, 1929) (Coleoptera: Cerambycidae) in Serbia - Milivojević, Tamara (Acta entomologica slovenica (Ljubljana), 2011)
Informations on the first finding of Paraboarmia viertlii (Bohatsch, 1883) in Slovenia are presented. It was collected on light traps near Podgorje in the Kras (Karst).
Keywords: Cerambycidae; Coleoptera; Dorcadion (Pedestrodorcadion) kaimakcalanum; favna; hrošči; prve najdbe; Serbia; Srbija